2015
DOI: 10.1080/10503307.2015.1078517
|View full text |Cite
|
Sign up to set email alerts
|

Racial/ethnic disparities in client unilateral termination: The role of therapists’ cultural comfort

Abstract: Therapists' racial/ethnic comfort may help explain disparities in unilateral termination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
150
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(160 citation statements)
references
References 44 publications
10
150
0
Order By: Relevance
“…clinical skilfulness in delivering the therapy) rather than experience (years of practicing a therapy) can make a critical difference to a patient's experience. 16 Also, several studies highlight that the general competence of a therapist is not synonymous with either their cultural competence 17,18 or level of comfort in discussing sexuality. 19,20 Conclusions Empirical research on the negative effects of psychotherapy is insufficient, partly because there is a lack of a coherent framework for defining, discussing and monitoring issues such as unwanted events, adverse reactions, malpractice reactions or deterioration of illness.…”
Section: Discussionmentioning
confidence: 99%
“…clinical skilfulness in delivering the therapy) rather than experience (years of practicing a therapy) can make a critical difference to a patient's experience. 16 Also, several studies highlight that the general competence of a therapist is not synonymous with either their cultural competence 17,18 or level of comfort in discussing sexuality. 19,20 Conclusions Empirical research on the negative effects of psychotherapy is insufficient, partly because there is a lack of a coherent framework for defining, discussing and monitoring issues such as unwanted events, adverse reactions, malpractice reactions or deterioration of illness.…”
Section: Discussionmentioning
confidence: 99%
“…Therapists need to be able to fluidly engage with clients who express a range of worldviews or behaviours (Owen, ). Comfort may be cultivated as clinicians develop awareness of their own identities and biases (Owen et al , ). Given the importance of increasing the capacity of CALD treatment providers, training and education programmes also need to be compatible with cultural practices (Robertson et al , ).…”
Section: Cultural Competence Trainingmentioning
confidence: 99%
“…Clinicians are one of the primary sources of racial/ethnic disparities in mental health treatment outcome (Hayes, Owen, & Bieschke, 2015;Imel et al, 2011;Larrison, Schoppelrey, Hack-Ritzo, & Korr, 2011;Owen, Imel, Adelson, & Rodolfa, 2012). Owen et al (2015) argue that racial/ethnic disparities emerge mainly when differential outcomes between CALD and mainstream clients within therapist caseloads are examined. For example, Imel et al (2011) found that variability in client's reduction of cannabis abuse was related to cultural factors of clients within therapist caseloads; i.e, the clinicians had better outcomes with CALD than mainstream clients, or the opposite.…”
Section: Cultural Competence In Practicementioning
confidence: 99%
See 2 more Smart Citations